Immunohistochemical Demonstration of Mast Cells in Bovine Papillomatous Digital Dermatitis of Holstein-Friesian Dairy Cattle - Ozguden-Akkoc, CG; Akkoç, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Mast cells (MC)are unique members of immune system; their location and functions are of great importance in health and disease status. This study aims to evaluate MCs distribution and heterogenity in healthy and digital dermatitis lesions of dairy cattle for the first time. A total of 50 skin samples, 25 healthy and 25 with digital dermatitis (DD) lesions were sampled in Holstein-Friesian dairy cattle. All samples were stained with hematoxylin-eosin (H&E) for microscopic examination and also stained with Toluidine blue for MCs demonstration. Epidermal acanthosis and hyperkeratosis with dermal inflammatory cell infiltrations were in consistent with digital dermatitis lesions. Spirochetal agents were successfully demonstrated with Warthin-Starry staining in 22 out of 25 DD samples. Increased number of mast cell were observed in digital dermatitis samples when compared with healthy skin samples. The average number of intact MCs were 4.6 ± 2 and 9.3 ± 1 in healthy and digital dermatitis samples, respectively. Two-fold increase in the number of intact MCs in digital dermatitis samples was observed. Degranulated mast cell numbers in tissue sections were also higher in digital dermatitis samples and 4.25-fold increase was recorded in affected skin samples. Immunophenotype of MCs in skin samples were identified by immmunohistochemical stainings with anti-tryptase and chymase antibodies. Only tryptase positive MCs were observed in healthy and DD samples. In the statistical analysis, differences in the mean intact and degranulated MCs were found to be significant (mean intact: p<0.05, mean degranulated: p<0.01). Our results possibly suggest that MCs may have important roles in the pathogenesis of bovine digital dermatitis.